2019
DOI: 10.1177/1087054719879487
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial Working Memory Capacity in the Brain After Working Memory Training in College Students With ADHD: A Randomized Controlled Trial

Abstract: Objective: ADHD has been associated with persistent problems of working memory. This study investigated the efficacy of an intensive and adaptive computerized working memory treatment (CWMT) at behavioral and neural levels. Method: College students ( n = 89; 40 females) with ADHD were randomized into a standard-length CWMT (45 min/session, 25 sessions, n = 29), shortened-length CWMT (15 min/session, 25 sessions, n = 32), and a waitlist group ( n = 28). Both CWMT groups received treatment for 5 days a week for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In our current paper, we did not observe group effects (i.e., differences between controls and ADHD) on the measurements of PGT due to the working memory training, other than on the response times ( Table 2). Our finding is in agreement with the observation that working memory training in general improves processing speed and attention performance [87] independently of the transfer to fluid intelligence [24,62,79] and that inattentive symptoms in ADHD are not associated with fluid intelligence [78,79,88] Hence, we do not discuss further the gambling task-related ERP components but P1 and LPN, the wave components which appeared to be the most affected by dual n-back task working memory training.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our current paper, we did not observe group effects (i.e., differences between controls and ADHD) on the measurements of PGT due to the working memory training, other than on the response times ( Table 2). Our finding is in agreement with the observation that working memory training in general improves processing speed and attention performance [87] independently of the transfer to fluid intelligence [24,62,79] and that inattentive symptoms in ADHD are not associated with fluid intelligence [78,79,88] Hence, we do not discuss further the gambling task-related ERP components but P1 and LPN, the wave components which appeared to be the most affected by dual n-back task working memory training.…”
Section: Discussionsupporting
confidence: 88%
“…If we consider all these observations together we may raise the hypothesis that WMT with the dual n-back task is able to generate a transfer effect in the PGT [111,112], as revealed by the LPN associated with a continued evaluation of contextual information in our PGT. This effect is strong in controls, but it is absent in our ADHD group, thus suggesting that the kind of WMT performed by our group of patients only confers benefits for those tasks that were trained [15,62,113]. We could speculate that a deficit in transfer effects associated with WM training could be associated with the abnormal parietal brain function observed in ADHD [114].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…From the previous WM training research, the brain regions where P3 amplitude enhanced or P3 latency reduced after training mainly involved frontal lobe as well as parietal lobe (Chen et al, 2019;Covey et al, 2018;Gajewski & Falkenstein, 2018), that is, WM training led to increased amplitudes and shortened latencies of P3a and P3b. However, there are a few studies which obtained inconsistent results (Liu et al, 2016;Woltering et al, 2021). Two studies found that there was no convincing evidence that the WM training per se changes neural activation patterns of behavioral tasks in Attention Deficit and Hyperactivity Disorder (ADHD) adults (Liu et al, 2016;Woltering et al, 2021).…”
mentioning
confidence: 99%
“…However, there are a few studies which obtained inconsistent results (Liu et al, 2016;Woltering et al, 2021). Two studies found that there was no convincing evidence that the WM training per se changes neural activation patterns of behavioral tasks in Attention Deficit and Hyperactivity Disorder (ADHD) adults (Liu et al, 2016;Woltering et al, 2021). Thus, it remains an open question whether WM training could lead to increased amplitudes and shortened latencies of P3a and P3b.…”
mentioning
confidence: 99%